Self-compacting concrete and preparation method thereof
By using mixed fibers of steel fiber and sisal fibers in self-finished concrete, as well as fly ash and modified steel slag powder, the problem of cracks caused by shrinkage of self-finished concrete is solved, and the strength and permeability of concrete are improved.
Patent Information
- Application Number
- CN202411766391.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The shrinkage of existing self-finished concrete is large, resulting in the occurrence of harmful cracks and reduces the strength and permeability of the concrete.
Mixed fibers of steel fiber and sisal fiber are used as modifiers, combined with fly ash and modified steel slag powder, and the synergistic effect of fiber mixture, fly ash and steel slag powder can reduce the generation and expansion of harmful cracks, and improve the strength and permeability of concrete.
Through the synergistic action of fibers and blends, the shrinkage of self-finished concrete is significantly reduced, the generation of cracks is reduced, and the mechanical strength and permeability of concrete are improved.
Smart Images

Figure BDA0005169055000000061 
Figure BDA0005169055000000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a self-compacting concrete and a preparation method thereof. Background Art
[0002] Self-compacting concrete is a concrete that can flow and compact under its own gravity, and can completely fill the formwork even in the presence of dense steel bars, while obtaining good homogeneity and requiring no additional vibration. Self-compacting concrete has the advantages of strong fluidity, good filling, stability without segregation, simple construction process, and fast pouring speed. It is widely used in large-volume structural concrete and complex-shaped reinforcement projects such as high-rise buildings, port terminals, undersea tunnels, and cross-sea bridges.
[0003] When preparing self-compacting concrete, the mix ratio of admixtures, binders and coarse and fine aggregates is designed so that the yield stress of the concrete is reduced to a level sufficient to be overcome by the shear stress generated by its own weight, thereby increasing the fluidity of the concrete and providing it with sufficient plastic viscosity to allow the aggregate to be suspended in the cement slurry without segregation or bleeding problems, thus forming a dense and uniform cementitious structure.
[0004] The existing self-compacting concrete has a large shrinkage, which mainly includes the autogenous shrinkage and plastic shrinkage of the concrete. The shrinkage causes harmful cracks in the self-compacting concrete, which reduces the strength and impermeability of the concrete and affects its durability. Summary of the invention
[0005] In order to inhibit the autogenous shrinkage and plastic shrinkage of self-compacting concrete, reduce the generation of harmful cracks, and improve the strength and impermeability of self-compacting concrete, the present application provides a self-compacting concrete and a preparation method thereof.
[0006] The present application provides a self-compacting concrete and a preparation method thereof using the following technical solutions: In a first aspect, the present application discloses a self-compacting concrete comprising the following raw materials in parts by weight: 320-370 parts of cement; 800-840 parts of coarse aggregate; 750-780 parts of fine aggregate; 12-19 parts of fiber composition; Fly ash 55-70 parts; 20-35 parts of steel slag powder; 1-3 parts of water reducing agent; 140-175 parts of water; 8-14 parts of expansion agent; The fiber composition is a mixed fiber of steel fiber and sisal fiber, wherein the weight ratio of the steel fiber to the sisal fiber is (9-13):(3-6).
[0007] The above technical solution is adopted to modify the concrete by mixing steel fiber and sisal fiber. Steel fiber can play a role in strengthening and toughening, and sisal fiber has good fracture resistance. The synergy of the two is conducive to improving the mechanical strength and crack toughness of concrete, and inhibiting the generation and expansion of cracks. The use of expansion agent is conducive to compensating the shrinkage of concrete and improving impermeability. Fly ash and steel slag powder are used as admixtures. The addition of steel slag powder is conducive to improving the shrinkage of self-compacting concrete and improving volume stability. Therefore, through the synergistic effect of fiber mixture, fly ash and steel slag powder, the generation and expansion of harmful cracks can be reduced, and the strength and impermeability of self-compacting concrete can be improved.
[0008] Optionally, the sisal fiber is modified sisal fiber, and the modified sisal fiber is made of the following raw materials in parts by weight: 3-5 parts of sisal fiber; 25-35 parts of 15% NaOH solution; 4-7 parts of methyl methacrylate; 0.2-0.5 parts of ammonium cerium nitrate.
[0009] By adopting the above technical scheme, alkali + methyl methacrylate are used to modify the sisal fiber, so as to remove impurities such as hemicellulose and lignin in the sisal fiber, enhance the bonding strength between the sisal fiber and the cement substrate and the reinforcement effect on the concrete, and facilitate the role of the sisal fiber in improving the fracture toughness. By grafting methyl methacrylate, the hydrophobicity of the modified sisal fiber is improved, the water bleeding phenomenon is weakened, and the anti-seepage performance is improved.
[0010] Optionally, the steel slag powder is modified steel slag powder, which is produced by mixing steel slag and a modifier, pressing them into a shape, and then calcining them at a high temperature and magnetically separating them. The modifier is composed of silicon dioxide and coal gangue, and the mass ratio of steel slag, silicon dioxide and coal gangue is (7-8):1:(1.8-2.2).
[0011] By adopting the above technical scheme, the free calcium oxide in the steel slag will cause the steel slag cement to crack, resulting in poor activity of the steel slag and poor volume stability. The chemical composition of the steel slag is adjusted by the modifier, the content of free calcium oxide is reduced, and the activity and wear resistance of the modified steel slag powder are improved, thereby playing a role in compensating for the shrinkage of concrete and improving the mechanical properties.
[0012] Optionally, the cement is ordinary Portland cement of grade P.O42.5, and the fly ash is selected from one of grade I fly ash and grade II fly ash.
[0013] By adopting the above technical solution, the addition of fly ash can better reduce the amount of cement added, thereby further controlling the hydration reaction, reducing the hydration heat, and enhancing the crack resistance of concrete.
[0014] Optionally, the coarse aggregate is continuous grade crushed stone with a particle size of 7-18 mm, and the fine aggregate is river sand with a fineness modulus between 2.2 and 2.5.
[0015] By adopting the above technical solution, the crushed stone has a larger particle size and a larger surface area, thereby increasing the volume of the concrete and stabilizing it; the river sand plays a filling role, reducing the porosity of the concrete and increasing the strength of the concrete.
[0016] Optionally, the water reducer is selected from one of a polycarboxylate water reducer and an aliphatic hydroxy sulfonate high-efficiency water reducer.
[0017] By adopting the above technical solution, the water reducing agent can reduce the addition of water, reduce the water-cement ratio of concrete, and improve the slump of concrete.
[0018] Optionally, the expansion agent is one or more of calcium sulfoaluminate, calcium oxide, and calcium sulfate.
[0019] By adopting the above technical solution, the expansive agent can expand during the hardening process of concrete, compensate for shrinkage, reduce the generation of cracks, and improve the anti-seepage performance.
[0020] Optionally, the steel fiber has a fiber diameter of 200-400 μm and a length of 30-40 mm, and the sisal fiber has a fiber diameter of 50-80 μm and a length of 20-25 mm.
[0021] By adopting the above technical scheme, the steel fibers and sisal fibers with the above diameters and lengths are well dispersed in concrete and have better comprehensive performance.
[0022] In a second aspect, the present application discloses a method for preparing self-compacting concrete, comprising the following steps: The coarse aggregate, fine aggregate, fiber composition, fly ash, steel slag powder and expansion agent are stirred to form a mixture; cement is added to the mixture and stirred, and then a water reducing agent and water are added and further stirred to obtain a self-compacting concrete.
[0023] By adopting the above technical scheme, the preparation method of the self-compacting concrete of the present application is simple and controllable, has strong operability, and the produced concrete has good fluidity and self-compactness.
[0024] When the sisal fiber is modified sisal fiber, the modified sisal fiber is prepared by the following steps: The sisal fibers are soaked in a 15% by mass NaOH solution for 1-1.5 hours, taken out and washed with deionized water until neutral, and then dispersed and placed in an oven at 90-100° C. and dried for 9-10 hours to obtain alkali-treated sisal fibers; Under a nitrogen atmosphere, alkali-treated sisal fiber and methyl methacrylate are placed in an acetone-water mixed solvent with an acetone mass fraction of 20%, and ammonium cerium nitrate is added as an initiator. The mixture is reacted at 45-50°C for 3-4 hours, and then the fibers are taken out and washed with deionized water, and then dispersed and placed in an oven at 90-100°C for drying for 9-10 hours to obtain modified sisal fiber.
[0025] By adopting the above technical scheme, the sisal fiber is firstly treated with alkali to remove low molecular weight impurities, and then methyl methacrylate is used to react with the hydroxyl group of the sisal fiber to achieve the modification of the sisal fiber and improve the interaction between the sisal fiber and the cement substrate.
[0026] In summary, this application has the following beneficial effects: 1. The concrete is modified by mixing steel fiber and sisal fiber. Steel fiber can play a role in strengthening and toughening, and sisal fiber has good fracture resistance. The synergy of the two is conducive to improving the mechanical strength and crack toughness of concrete, and inhibiting the generation and expansion of cracks; the use of expansion agent is conducive to compensating the shrinkage of concrete and improving impermeability. Fly ash and steel slag powder are used as admixtures. The addition of steel slag powder is conducive to improving the shrinkage of self-compacting concrete and improving volume stability. Therefore, through the synergistic effect of fiber mixture, fly ash and steel slag powder, the generation and expansion of harmful cracks can be reduced, and the strength and impermeability of self-compacting concrete can be improved.
[0027] 2. Use alkali + methyl methacrylate to modify the sisal fiber, remove impurities such as hemicellulose and lignin in the sisal fiber, enhance the bonding strength between the sisal fiber and the cement substrate and the reinforcement effect on the concrete, and help the sisal fiber to improve the fracture toughness. By grafting methyl methacrylate, the hydrophobicity of the modified sisal fiber is improved, the water seepage phenomenon is weakened, and the anti-seepage performance is improved. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0029] The cement used is P.O42.5 grade ordinary Portland cement from Wuhan Yadong Cement; The fly ash is grade I fly ash or grade II fly ash from Hunan Sanlin New Materials Co., Ltd. Fine aggregate: river sand, fineness modulus: 2.3; Coarse aggregate: Yangxin crushed stone, nominal size: 7-18mm; The polycarboxylate water reducer was purchased from Wuhan Huaxuan High-tech Co., Ltd., model HX-YZJ01; Aliphatic hydroxysulfonate high-efficiency water reducer was purchased from Jiangsu Lianxiong Fine Chemical Technology Co., Ltd.; The expansion agent was purchased from Wuhan Chenlong New Materials Technology Co., Ltd.; Steel slag powder was purchased from Hebei Angyun Mineral Products Co., Ltd. The steel fibers were purchased from a material company in Hengshui City, Hebei Province, with an average length of 30 mm and an average fiber diameter of 300 μm; Sisal fiber was purchased from Hengwei Hemp Products Factory in Changge City, Henan Province, with an average length of 20 mm and an average fiber diameter of 60 μm.
[0030] Preparation Example Preparation Example 1 Modified sisal fiber, composed of the following raw materials: 3kg sisal fiber; 25kg of 15% NaOH solution; Methyl methacrylate 4kg; 0.2kg of cerium ammonium nitrate.
[0031] The modified sisal fiber is prepared by the following steps: The sisal fibers were soaked in a 15% by mass NaOH solution for 1 hour, washed with deionized water for 3-4 times until neutral, and then dispersed and dried in an oven at 90° C. for 9 hours to obtain alkali-treated sisal fibers; Under a nitrogen atmosphere, alkali-treated sisal fiber and methyl methacrylate were placed in 30 kg of acetone-water mixed solvent with a mass fraction of 20% acetone, and ammonium cerium nitrate was added as an initiator. The mixture was reacted at 45°C for 3 hours, and then washed with deionized water, dispersed and placed in an oven at 90°C for 9 hours to obtain modified sisal fiber.
[0032] Preparation Example 2 Modified sisal fiber, composed of the following raw materials: 5kg sisal fiber; 35kg of 15% NaOH solution; Methyl methacrylate 7kg; 0.5kg of cerium ammonium nitrate.
[0033] The modified sisal fiber is prepared by the following steps: The sisal fibers were soaked in a 15% by mass NaOH solution for 1.5 hours, washed with deionized water for 3-4 times until neutral, and then placed in an oven at 100° C. and dried for 10 hours to obtain alkali-treated sisal fibers; Under a nitrogen atmosphere, alkali-treated sisal fiber and methyl methacrylate were placed in 40 kg of acetone-water mixed solvent with a mass fraction of 20% acetone, and ammonium cerium nitrate was added as an initiator. The mixture was reacted at 50°C for 4 hours, washed with deionized water, and dispersed in an oven at 100°C for 10 hours to obtain modified sisal fiber.
[0034] Preparation Example 3 Modified steel slag powder is composed of the following raw materials: Steel slag 7kg; Modifier: 1kg of silicon dioxide; 1.8kg of coal gangue.
[0035] The modified steel slag powder is prepared by the following steps: Add steel slag and modifier into the reactor, heat to 1300℃, and calcine for 20min; then cool to 1100℃ and keep warm for 1.5h. After the heat preservation, take out the steel slag and put it into water for rapid cooling, so that the steel slag is quickly cooled from 1100℃ to room temperature; The taken out steel slag is ground and magnetically separated, and the iron-containing minerals are magnetically separated by a magnetic separation tube to obtain the iron-containing minerals, and the steel slag tailings obtained after magnetic separation are modified steel slag powder.
[0036] Preparation Example 4 Modified steel slag powder is composed of the following raw materials: 8kg steel slag; Modifier: 1kg of silicon dioxide; 2.2kg of coal gangue.
[0037] The modified steel slag powder is prepared by the following steps: Add steel slag and modifier into the reactor, heat to 1600℃, and calcine for 30min; then cool to 1300℃ and keep warm for 2.5h. After the heat preservation, take out the steel slag and put it into water for rapid cooling, so that the steel slag is quickly cooled from 1300℃ to room temperature; The taken out steel slag is ground and magnetically separated, and the iron-containing minerals are magnetically separated by a magnetic separation tube to obtain the iron-containing minerals, and the steel slag tailings obtained after magnetic separation are modified steel slag powder. Example
[0038] Example 1 800 kg of crushed stone, 750 kg of river sand, 12 kg of fiber composition, 55 kg of fly ash, 20 kg of steel slag powder and 8 kg of calcium sulphoaluminate expansion agent were added into a concrete mixer for first stirring for 6 min, and the fiber composition was selected from 9 kg of steel fiber and 3 kg of sisal fiber to obtain a mixed material; 320 kg of cement was added to the above mixture for a second stirring for 3 min, and then 1 kg of polycarboxylate water reducer and 140 kg of water were added for a third stirring for 1 min to obtain self-compacting concrete.
[0039] Embodiment 2-4 The differences between Examples 2 to 4 and Example 1 are the raw materials, raw material parameters and stirring time, as shown in Table 1.
[0040] In Example 2, 19 kg of the fiber composition is specifically selected from 13 kg of steel fiber and 6 kg of sisal fiber, the expansion agent is selected from calcium oxide expansion agent, and the water reducing agent is selected from polycarboxylate water reducing agent; In Example 3, 15 kg of the fiber composition specifically selected 10 kg of steel fiber and 5 kg of sisal fiber, the expansion agent selected calcium sulfate expansion agent, and the water reducing agent selected aliphatic hydroxysulfonate high-efficiency water reducing agent; In Example 4, 15 kg of the fiber composition is specifically selected from 9 kg of steel fiber and 6 kg of sisal fiber, the expansion agent is selected from calcium sulfoaluminate expansion agent, and 2 kg of water reducer is specifically selected from 1 kg of polycarboxylic acid water reducer and 1 kg of aliphatic hydroxysulfonate high-efficiency water reducer.
[0041] Table 1 Example 5 The difference between this embodiment and embodiment 1 is that in the raw materials of the self-compacting concrete, 3 kg of the modified sisal fiber prepared in preparation example 1 is used to replace the sisal fiber of the same mass.
[0042] Example 6 The difference between this embodiment and embodiment 1 is that in the raw materials of the self-compacting concrete, 3 kg of the modified sisal fiber prepared in preparation example 2 is used to replace the sisal fiber of the same mass.
[0043] Example 7 The difference between this embodiment and embodiment 1 is that in the raw materials of the self-compacting concrete, 20 kg of the modified steel slag powder prepared in preparation example 3 is used to replace an equal mass of steel slag powder.
[0044] Example 8 The difference between this embodiment and embodiment 1 is that in the raw materials of the self-compacting concrete, 20 kg of the modified steel slag powder prepared in preparation example 4 is used to replace an equal mass of steel slag powder.
[0045] Example 9 The difference between this embodiment and embodiment 1 is that in the raw materials of self-compacting concrete, 3 kg of modified sisal fiber prepared in preparation example 2 is used to replace an equal mass of sisal fiber, and 20 kg of modified steel slag powder prepared in preparation example 3 is used to replace an equal mass of steel slag powder.
[0046] Example 10 The difference between this embodiment and embodiment 1 is that in the raw materials of self-compacting concrete, 3 kg of modified sisal fiber prepared in preparation example 1 is used to replace an equal mass of sisal fiber, and 20 kg of modified steel slag powder prepared in preparation example 4 is used to replace an equal mass of steel slag powder.
[0047] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that in the raw materials of the self-compacting concrete, 3 kg of steel fiber is selected to replace the sisal fiber of the same mass.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that in the raw materials of the self-compacting concrete, 9 kg of sisal fiber is selected to replace the steel fiber of the same mass.
[0049] Comparative Example 3 The difference between this comparative example and Example 1 is that 20 kg of steel slag powder is not added to the raw materials of the self-compacting concrete.
[0050] Performance test experiment The compressive strength, autogenous shrinkage, crack resistance and impermeability of the self-compacting concretes prepared in Examples 1-10 and Comparative Examples 1-3 were tested.
[0051] Compressive strength: According to GB / T 50081-2002, the concrete obtained in each embodiment of the present invention and the comparative example was made into a test piece, and the compressive strength test was performed on each test piece to detect the compressive strength of the concrete after curing for 28 days. The test results are shown in Table 2.
[0052] Autogenous shrinkage performance: The concrete specimens with a size of 100 mm*100 mm*515 mm were sealed with plastic wrap, and the autogenous shrinkage rate of the concrete was tested by a CABR-NES non-contact shrinkage deformation instrument at (20±2)°C. The test results are shown in Table 2.
[0053] Anti-seepage performance: The water seepage height of concrete was tested according to the step-by-step pressurization method in GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The sample size penetration pressure was 3.5MPa and the pressurization time was 48h. The test results are shown in Table 2.
[0054] Table 2 Sample Compressive strength(MPa) <![CDATA[Self-shrinkage rate (10 -6 m / m)]]> Water seepage height (mm) Example 1 46.7 242 0.28 Example 2 47.3 240 0.28 Example 3 48.1 243 0.27 Example 4 47.6 238 0.26 Example 5 51.9 228 0.20 Example 6 52.2 229 0.21 Example 7 56.3 208 0.24 Example 8 55.8 206 0.22 Example 9 60.4 170 0.17 Example 10 60.8 173 0.16 Comparative Example 1 41.5 562 1.67 Comparative Example 2 35.9 268 0.85 Comparative Example 3 38.6 292 0.54 According to Table 2, the self-compacting concrete of Examples 1-4 uses a mixture of steel fiber and sisal fiber to modify the self-compacting concrete. The mixed fiber can fill the voids inside the concrete, form an effective bridge effect to limit the expansion of cracks, and improve the fracture toughness and cracking toughness of the concrete; the addition of steel slag can reduce the porosity of the concrete, improve the adhesion between aggregate and slurry, and improve the mechanical properties of the concrete; at the same time, the hydrate on the surface of the steel fiber can enhance the adhesion between the matrix and the fiber, and the internal fineness of the steel slag is reasonably planned to improve the overall dispersibility and compatibility. Therefore, through the synergistic effect of steel fiber, sisal fiber and steel slag, the self-compacting concrete has excellent compressive strength, and the crack resistance and impermeability are enhanced.
[0055] Compared with Example 1, Example 5-6 uses modified sisal fiber. The water resistance of the sisal fiber after alkali treatment and methyl methacrylate grafting is improved, small molecular impurities are removed, and the uniform dispersion and adhesion in the cement matrix are improved, which is beneficial for the sisal fiber to exert its crack resistance and impermeability performance.
[0056] Compared with Example 1, Example 7-8 uses modified steel slag powder. The steel slag is modified by silicon dioxide and coal gangue, which reduces the content of free calcium oxide in the steel slag, increases the activity of the steel slag, reduces the cracking of concrete, and improves the mechanical properties and shrinkage resistance of the concrete.
[0057] Compared with Example 1, in Comparative Examples 1 and 2, steel fiber and sisal fiber are used in the raw materials of self-compacting concrete respectively. The steel fiber is evenly distributed in the concrete matrix to play a reinforcing role, which has a great influence on the compressive strength, while the sisal fiber has good tensile strength, which can effectively improve the toughness and flexural resistance of concrete and inhibit the generation and development of cracks. The steel fiber and sisal fiber synergistically play a positive hybrid effect, and the comprehensive performance is better than that of a single fiber.
[0058] Compared with Example 1, in Comparative Example 3, no steel slag powder was added to the raw materials of the self-compacting concrete. The addition of steel slag powder can enhance the compressive strength, impermeability and flexural strength of the concrete, so the overall performance of Comparative Example 3 is reduced.
[0059] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A self-compacting concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 320-370 parts of cement; 800-840 parts of coarse aggregate; 750-780 parts of fine aggregate; 12-19 parts of fiber composition; Fly ash 55-70 parts; 20-35 parts of steel slag powder; 1-3 parts of water reducing agent; 140-175 parts of water; 8-14 parts of expansion agent; The fiber composition is a mixed fiber of steel fiber and sisal fiber, wherein the weight ratio of the steel fiber to the sisal fiber is (9-13):(3-6).
2. A self-compacting concrete according to claim 1, characterized in that: The sisal fiber is modified sisal fiber, and the modified sisal fiber is made of the following raw materials in parts by weight: 3-5 parts of sisal fiber; 25-35 parts of 15% NaOH solution; 4-7 parts of methyl methacrylate; 0.2-0.5 parts of ammonium cerium nitrate.
3. The self-compacting concrete according to claim 1, characterized in that: The steel slag powder is modified steel slag powder, which is produced by mixing steel slag and a modifier, pressing and molding, and then calcining at high temperature and magnetic separation. The modifier is composed of silicon dioxide and coal gangue, and the mass ratio of steel slag, silicon dioxide and coal gangue is (7-8):1:(1.8-2.2).
4. The self-compacting concrete according to claim 1, characterized in that: The cement is ordinary Portland cement of grade P.O42.5, and the fly ash is selected from one of grade I fly ash and grade II fly ash.
5. The self-compacting concrete according to claim 1, characterized in that: The coarse aggregate is continuous grade crushed stone with a particle size of 7-18 mm, and the fine aggregate is river sand with a fineness modulus between 2.2 and 2.
5.
6. The self-compacting concrete according to claim 1, characterized in that: The water reducer is selected from one of a polycarboxylic acid water reducer and an aliphatic hydroxysulfonate high-efficiency water reducer.
7. The self-compacting concrete according to claim 1, characterized in that: The expansion agent is selected from one or more of calcium sulfoaluminate, calcium oxide, and calcium sulfate.
8. The self-compacting concrete according to claim 1, characterized in that: The steel fiber has a fiber diameter of 200-400 μm and a length of 30-40 mm, and the sisal fiber has a fiber diameter of 50-80 μm and a length of 20-25 mm.
9. A method for preparing a self-compacting concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: The coarse aggregate, the fine aggregate, the fiber composition, the fly ash, the steel slag powder and the expansion agent are stirred to form a mixed material; Cement is added to the mixture and stirred, and then a water reducing agent and water are added and further stirred to obtain self-compacting concrete.
10. A method for preparing a self-compacting concrete according to claim 9, characterized in that: When the sisal fiber is modified sisal fiber, the modified sisal fiber is prepared by the following steps: The sisal fibers are soaked in a 15% by mass NaOH solution for 1-1.5 hours, taken out and washed with deionized water until neutral, and then dispersed and placed in an oven at 90-100° C. and dried for 9-10 hours to obtain alkali-treated sisal fibers; Under a nitrogen atmosphere, the alkali-treated sisal fiber and methyl methacrylate were placed in an acetone-water mixed solvent with an acetone mass fraction of 20%, and ammonium cerium nitrate was added as an initiator. The mixture was reacted at 45-50°C for 3-4 hours, and then washed with deionized water, dispersed and placed in an oven at 90-100°C for 9-10 hours to obtain modified sisal fiber.
Citation Information
Patent Citations
Steel slag high-temperate modification method
CN104016600A
Method for preparing sisal fiber-reinforced starch composite material
CN107540880A
High-strength pervious concrete and preparation method thereof
CN111233395A
High-strength self-compacting concrete and preparation method thereof
CN112919863A
Anti-crack concrete for super-long structure and preparation method thereof
CN113149556A
Cited By
Anti-cracking calcium silicate board and preparation method thereof
CN121850533A
A crack-resistant calcium silicate board and its preparation method
CN121850533B